Does foreign aid promote democracy? Aid, democracy, and instability from trade - Thierry Kangoye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study revisits the effect of aid on the quality of institutions and examines the effects of a major source of instability, namely terms-of-trade instability, on the quality of democracy. We take advantage of previous empirical findings which explain the role of aid in mitigating the adverse effects of external shocks, and argue that in the long term, aggregate aid flows can potentially dampen the effects of terms-of-trade instability on the quality of democracy. An empirical investigation with data from 71 developing countries (including 28 African states) over the period 1980-2003 provides supportive results.
Keywords: F35; F4; O11; O43; 330; democracy; foreign aid; terms-of-trade instability; Entwicklungshilfe; Terms of Trade; Demokratie; Entwicklungsländer